The investor in structured retail products : marketing driven or gambling oriented? - Abreu, Margarida (2017)
Structured retail products (SRP) are one of the most visible faces of financial innovation and are becoming increasingly popular amongst retail investors. However, there is strong consensus that retail investors’ preference for structured products is difficult to explain using the standard rational theory, those products being in general sold at a significant premium. Studying the actual trading behavior of individual investors we provide evidence consistent with the view that SRP likely offer value to some informed investors compared to other products, that product complexity is a way to complete markets and that SRP allow investors to access segments otherwise not available to them. Nonetheless, our results also suggest that the increasing popularity of SRP is deeply related to investors’ behavioral biases, particularly overconfidence and gambling. Moreover, results also show that SRP trading activity cannot be dissociated from aggressive marketing practices.